2012
DOI: 10.1016/j.ijrobp.2011.06.1999
|View full text |Cite
|
Sign up to set email alerts
|

Role of Insulin-Like Growth Factor-1 Signaling Pathway in Cisplatin-Resistant Lung Cancer Cells

Abstract: Purpose The development of drug-resistant phenotypes has been a major obstacle to Cisplatin (CDDP) use in non-small cell lung cancer (NSCLC). We aimed to identify some of the molecular mechanisms that underlie CDDP resistance by using microarray expression analysis. Methods and Materials H460 cells were treated with cisplatin. Differences between cisplatin-resistant lung cancer cells (CDDP-R) and parental H460 cells were studied using Western blot, MTS and clongenic assays, in vivo tumor implantation, and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 20 publications
3
52
0
Order By: Relevance
“…Bitelman et al [46] reported that cisplatin-resistant cells demonstrating increased activation of the IGF1 pathway recovered their sensitivity to cisplatin after small interfering RNA treatment. IGF1R activation has been known to protect tumor cells against apoptosis induced by cytotoxic drugs, and may also influence the repair of DNA damage [47]. From our research and the other results cited here, it is clear that activation of the IGF1 pathway is relevant to the maintenance of stemness.…”
Section: Discussionsupporting
confidence: 72%
“…Bitelman et al [46] reported that cisplatin-resistant cells demonstrating increased activation of the IGF1 pathway recovered their sensitivity to cisplatin after small interfering RNA treatment. IGF1R activation has been known to protect tumor cells against apoptosis induced by cytotoxic drugs, and may also influence the repair of DNA damage [47]. From our research and the other results cited here, it is clear that activation of the IGF1 pathway is relevant to the maintenance of stemness.…”
Section: Discussionsupporting
confidence: 72%
“…Increased IGF-1 receptor expression in NSCLC is associated with poor prognosis [93], and IGF-1 receptor expression was noted to be higher in hepatocellular carcinoma cancer stem cells [94]. Cisplatin resistant lung cancer cells were found to have increased IGF-1 receptor signaling [95]. …”
Section: Laboratory Evidence and The Basis For Further Clinical Trialsmentioning
confidence: 99%
“…However, Yamamoto et al (2012) claimed that IGF1R overexpression was related to lymph node metastasis and tumor recurrence. Also, Sun et al (2012) claimed that IGF1R expression played a role in the development of resistance to cisplatin and radiotherapy in NSCLC.…”
Section: Discussionmentioning
confidence: 99%